2005
DOI: 10.1177/039463200501800422
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with 1, 25-Dihydroxyvitamin D3 Preserves Glomerular Slit Diaphragm-Associated Protein Expression in Experimental Glomerulonephritis

Abstract: In this study, we investigated the effect of 1,25(OH)2D3 on proteinuria and on the alteration of slit diaphragm-associated proteins induced by anti-Thy 1.1 in Wistar rats. Four groups of animals were studied: group I, anti-Thy 1.1 treated rats; group II, anti-Thy1.1 treated group that at day 2, after the onset of overt proteinuria, started the treatment with 1,25(OH)2D3; group III, normal control rats injected with vehicle alone; group IV, rats that received only 1,25(OH)2D3. At day 2, in group I and II, befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 43 publications
0
36
0
4
Order By: Relevance
“…7,23 Animal studies have shown that elevated levels of active vitamin D contribute to factors that are hypothesized to be associated with a reduction of kidney disease progression, including reduction in proteinuria, decrease in TGF-b, inhibition of mesangial cell proliferation, and preservation of the structural integrity of glomerular podocytes. [24][25][26][27] Finally, FGF-23 might directly contribute to kidney injury, similar to the direct effect of FGF-23 on cardiac myocytes. 9 Previous studies suggest that FGF-23 elevation precedes abnormalities in other mineral metabolism markers, which supports the potential role of FGF-23 as an early indicator of renal pathology.…”
Section: Discussionmentioning
confidence: 94%
“…7,23 Animal studies have shown that elevated levels of active vitamin D contribute to factors that are hypothesized to be associated with a reduction of kidney disease progression, including reduction in proteinuria, decrease in TGF-b, inhibition of mesangial cell proliferation, and preservation of the structural integrity of glomerular podocytes. [24][25][26][27] Finally, FGF-23 might directly contribute to kidney injury, similar to the direct effect of FGF-23 on cardiac myocytes. 9 Previous studies suggest that FGF-23 elevation precedes abnormalities in other mineral metabolism markers, which supports the potential role of FGF-23 as an early indicator of renal pathology.…”
Section: Discussionmentioning
confidence: 94%
“…Active vitamin D analogues ameliorate renal function in a rat model of chronic allograft nephropathy, 29 in subtotally nephrectomized rats, 7,[30][31][32] and in other models of CKD. 8 34 reduction of glomerular inflammation, and reduction of tubular cell proliferation. 7 VDR signaling also interferes with important pathways of CKD progression, including the reninangiotensin system (RAS), 35 epidermal growth factor receptor, 36 and TGF-b signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, vitamin D signaling protects against progression of chronic renal lesions in different models of CKD. [7][8][9][10][11][12][13][14][15] More recently, calcitriol and paricalcitol, two agonists of VDR signaling, have been shown to lessen albuminuria in patients with IgA nephropathy 16 and diabetic nephropathy, 17 respectively. In addition, two community-based studies and a small observational study in patients with CKD who have not had transplantation found an association between low 25(OH)D levels and the risk of ESRD 18 or eGFR decline.…”
mentioning
confidence: 99%
“…39 In the anti-Thy 1.1 model of glomerulonephritis, rats treated with 1,25(OH) 2 D 3 had less albuminuria 40 and showed preserved slit diaphragm protein morphology. 9 22-Oxacalcitriol, a vitamin D analog, reduced urine albumin excretion and prevented mesangial cell proliferation and extracellular matrix expansion in two different rat models of glomerulosclerosis. 10,41 Mesangial cell proliferation and extracellular matrix expansion are two of the pathologic processes that lead to progressive glomerulosclerosis.…”
Section: Clinical Epidemiology Wwwjasnorgmentioning
confidence: 99%
“…Activated vitamin D, 1,25-dihydroxyvitamin D [1,25(OH)2D], suppresses renin biosynthesis in mice, and vitamin D deficiency stimulates renin production. 8 In different animal models, 1,25(OH)2D or its analogs reduced proteinuria levels; preserved glomerular podocyte structure 9 ; decreased levels of TGF-␤1, an inducer of renal fibrosis; and inhibited mesangial cell proliferation, a marker of renal injury. 10 Low 25(OH)D levels were associated with albuminuria in a cross-sectional analysis of NHANES III.…”
mentioning
confidence: 99%